CONSTRUCTION WORK TASKS DURATION: NEW METHOD OF ESTIMATION AND QUALITY CONTROL - Bovteev, Sergei; Kanyukova, Svetlana; Okrepilov, Vladimir; Rezvaia, Anna (Journal of Applied Engineering Science, 2016)
The article considers the principles of ensuring the completion of construction projects to meet the date. The authors suggest the method of assessing the progress of the project and estimating timely completion of the project based on the application of the Schedule Timeless Index (STI) and the Schedule Progress Index (SPI). The method allows to analyze dynamically the deviation of the timing of the project for prompt adoption of effective management decisions